Penumbra on the cultural zone of Metropolitan Lima. An analysis of the management processes of the huaca San Borja (Lima-Perú) between the years 1986-2016 - Chambi Echegaray, Peruska (2019)
The process of revaluing the built heritage of the Huaca San Borja, located within the metropolitan area of the capital of Peru, Lima, ran from 1986 to 2016. During these years and due to changes in government, and thence, in the orientation of public institutions, the management processes initiated after various agreements did not comply with placing this important heritage into social use, and today, construction work for its revaluation is still happening. On the other hand, in the different stages of the process, the local neighbors’ participation was not contemplated. The public and private entities that were in charge did not communicate that work would be done, much less how they would be linked to the project, given that they would be the main custodians of this archaeological heritage. This study analyzes the three management processes that the Huaca San Borja went through and how each of them influenced its recovery and revaluation.